2022
DOI: 10.52520/masjaps.v7i2id189
|View full text |Cite
|
Sign up to set email alerts
|

Lentil (Lens culinaris Medik.): A Current Review

Abstract: Lentil was first cultivated 8000–10,000 years ago and is a protein-rich crop. It is an important dietary component in many Mediterranean and Asian countries but allergic reactions to lentil intake was reported in some countries. Lentil yield is a key and difficult trait to enhance for crop genetic improvement. Several biotic and abiotic variables such as drought, high temperature, salinity, mineral deficiency and fungal diseases limit the production of lentils. Landraces and wild relatives are more tolerant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Drought stress is the most important factor that has serious harmful effects on the growth and development of lentil (Zeroual et al, 2022). It has been found that up to 50% yield losses occur in the production of lentil exposed to drought (Mart, 2022). Drought significantly inhibits lentil emergence, germination and seedling growth.…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress is the most important factor that has serious harmful effects on the growth and development of lentil (Zeroual et al, 2022). It has been found that up to 50% yield losses occur in the production of lentil exposed to drought (Mart, 2022). Drought significantly inhibits lentil emergence, germination and seedling growth.…”
Section: Introductionmentioning
confidence: 99%